Implementation of Bible integration to increase the value of multiculturalism in integrated social studies learning at christian junior high school - Riko Andarista; Leo Agung S; Suryo Ediyono (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The purpose of this research was to determine the application of the actualization of Bible integration through Integrated Social Studies learning using the Independent Learning Curriculum. This study uses a qualitative approach with a phenomenological design that seeks to reveal events in actual conditions. This study took place in several private Christian schools in Surakarta City. This study involved 17 teachers and 30 students in grades 7, 8, and 9 of Pelita Nusantara Kasih Surakarta Christian Middle School, with diverse religious and regional backgrounds. The key informants were social studies teachers, while additional informants were students as research subjects. The data collection techniques used were observation and interviews, interactive model data analysis techniques from Miles and Huberman (quoted) in the form of data collection, data reduction, data presentation, and drawing conclusions. To test the validity of the data, a credibility test was used through triangulation and member checking. This study found that Christian schools have students with diverse ethnic, racial, and religious backgrounds. Through the integration of the Bible in social studies learning, students are guided to show respect and concern amidst the diversity of tribes, races, and religions in a multicultural school environment.